Zorla tıbbi müdahale - Azgın, Nermin (İstanbul Medipol Üniversitesi Sosyal Bilimler Enstitüsü, 2021)
Tezimizde, hukuka uygunluk şartları bakımından hangi müdahalelerin zorla tıbbi müdahale niteliği taşıdığı ve bu müdahaleler sonucunda hastaların hangi yetkili mercilere başvuracağı konusu ele alınmıştır. Bu bağlamda bir yandan geçerli rızanın şartları, özellikle hastanın gereği gibi aydınlatılması konusu tartışılırken, rızanın eksikliği halinde onun yerini dolduracağı kabul edilen varsayılan rıza kavramı incelenmiştir. Öte yandan; zorla tıbbi müdahale sınıflandırılarak cinsiyet değişikliği, sünnet, kastrasyon, beden muayaneleri, genital muayane, ötanazi ve tedaviyi red hakkı gibi tartışmalı alanlarda hastanın ve özellikle ayırt etme yetisine sahip küçük ve kısıtlıların rızası açısından ortaya çıkan sorunlar üzerinde durulmuştur. Bununla birlikte, mevzuatımızın hasta hakları ihlallerinde hasta ve hasta yakınlarına hukuki, idari ve cezai olmak üzere sağladığı korunma imkanları irdelenmiştir. İhlal edilen hasta hakları konusunda mevzuatımızdaki düzenlemeler kapsamında başvuru hakkı ve bu hakkın kullanılması bakımından görevli ve yetkili kurumlar ele alınmıştır.

In our thesis it will be evaluated which interventions are forced medical interventions according to the requirements of the legality and the legal remedies of the patients affected by these interventions. In this context, the current consent requirements, especially İnforming the patient properly, are discussed on the one hand and the concept of presumed consent is examined as replacing the informed consent in case of lack of it on the other hand. Also it is emphasized that as types of medical interventions castration, gender change, circumcision, castration, body examinations, genital examination, organ and tissue transplants, euthanasia and the right to refusal of treatment are discussed areas, and there are problems about patients' and in particular competent minors and wards who has the power to distinguish. In addition, legal, administrative and criminal remedies which are prescribed by our laws to protect patient and its relatives in case of violation of patients rights are examined. Moreover authorities which are legally competent to recieve individual applications on the alleged violations of patients' rights are evaluated.
Forced medical intervention
Keywords: Sağlık Hukuku; Tıbbi Müdahale; Aydınlatılmış Onam; Varsayılan Rıza; Başvuru Hakkı; Başvuru Mercileri; Health Law; Medical Intervention; Informed Consent; Presumed Consent; Right to Apply; Authorities to Apply